Inculcating of sasak local cultural values in learning at elementary school - Aswasulasikin Aswasulasikin; Dina Fadilah; Yul Alfian Hadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This study aims at exploring information about inculcating Sasak local cultural values through learning. Designed using descriptive qualitative through interviews, observations and documentation, this study used teachers, principals, and students in the district of East Lombok as informants that chosen randomly. The data obtained can be described as follows: first, the majority of local sasak cultures are almost extinct due to the rapid development of technology that exhibits external cultures that are easily accessed by the younger generation, while the local culture of the Sasak cannot keep up with these technological developments. Second, the inculcation of local culture through learning at school cannot be carried out because there are no guidelines as a reference for curriculum and policy development from the government (east Lombok education department). Third, there is no Sasak local culture curriculum that can be used as a reference in learning in elementary schools. Most elementary school students do not know Sasak culture because most schools cannot instill Sasak cultural values through learning as a culture that must be understood and as a guide in students’ daily life. As the results, Elementary school students are more familiar with various types of Indian and western dance and food rather than their their own culture.